1994
DOI: 10.2220/biomedres.15.95
|View full text |Cite
|
Sign up to set email alerts
|

<b><i>IN VITRO</i> AUTORADIOGRAPHIC DEMONSTRATION OF ENDOTHELIN-1 BINDING SITES IN THE HUMAN ADRENAL </b><b>CORTEX </b>

Abstract: Endothelin-l (ET-1) is a 21-amino acid peptide secreted by endothelial cells, that exerts a potent vasoconstrictor action. Two subtypes of ET-1 receptors have been recently identified: ETA and ETB, which are expressed by vascular smooth-muscle cells and endothelium, respectively. Compelling evidence indicates that ET-1 exerts a strong secretagogue effect on adrenal zona glomerulosa (ZG), but not zona fasciculata (ZF) in vivo and in vino; therefore, We performed an autoradiographic study of the occurrence of ET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1996
1996
1999
1999

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…There was an ECE-1 gradient accross the zones of the adrenal gland, with the zona glomerulosa having the highest staining. Autoradiography has shown that ET-A receptors are limited exclusively to the zona glomerulosa, whereas ET-B receptors are found throughout the adrenal cortex (Belloni et al 1994). Davenport et al (1996) found that ET peptides and receptors were differentially distributed in the human adrenal gland.…”
Section: Discussionmentioning
confidence: 99%
“…There was an ECE-1 gradient accross the zones of the adrenal gland, with the zona glomerulosa having the highest staining. Autoradiography has shown that ET-A receptors are limited exclusively to the zona glomerulosa, whereas ET-B receptors are found throughout the adrenal cortex (Belloni et al 1994). Davenport et al (1996) found that ET peptides and receptors were differentially distributed in the human adrenal gland.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, the two endocrine systems within the adrenal form a functional unit, and an alteration in one system will certainly affect the other (15). It has recently been demonstrated that chromaffin cells are in close cellular contact with adrenocortical cells (14, 36 -38), immune cells (39,40), nerve cells (41), and endothelial cells (42) in normal adrenals. These paracrine intra-adrenal interactions within dif-ferent components of the adrenal are important for basal hormone production and play a role in the development, cell proliferation, circadian rhythm and zonation of the adrenal gland (15,(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56).…”
Section: Discussionmentioning
confidence: 99%
“…5). Accordingly, the autoradiographic quantitative analysis of [ 125 I]ET-1 binding and its displacement by selective ligands clearly demonstrated that ETB receptors are present throughout the entire adrenal cortex, whereas ETA receptors are restricted to the ZG (3,4,6,7).…”
mentioning
confidence: 99%